(untitled) (Al-Qamar, 2026)
The economic involvement of women in early Islam is discussed in this research paper by referring to the practical examples of the life of Rasulullah ﷺ and the supportive role of the Sahaba (RA). It also emphasises the fact that Islam gave women the right to own property, conduct businesses and trade in a dignified and Shariah compliant way. The paper examines the important individuals like Sayyidah Khadijah (RA) who was a successful businesswoman and other Sahabiyat (RA) who were involved in trade, education, agriculture, and healthcare. Particular attention has been given to the way the Prophet ﷺ motivated them to contribute and at the same time remained modest, family-responsible and morally modest. The contribution of Sahaba (RA), including Abu Bakr (RA), Umar (RA), and Abdur Rahman bin Auf (RA), to the economic activity of women is also discussed. Through the comparison of these practices with the current Muslim communities, this paper will demonstrate how the prophetic guidance is a balanced system that allows women to work, earn, and play a role in society without jeopardizing Islamic values. This paper concludes that women economic empowerment in the Muslim faith is not a new phenomenon but a tradition of prophetical backing of the Sahaba (RA).